การพัฒนาอัตมโนทัศน์ทางสังคมของนักศึกษาฝึกประสบการณ์วิชาชีพครูในศตวรรษที่ 21 ด้วยกิจกรรมตามแนวจิตตปัญญาศึกษา - ภักษา ภวิกา (Journal of Education Studies, Chulalongkorn University, 2019)
The purposes of this research were 1) to develop contemplative activities based on contemplative education, and to study the effects of these approaches; 2) to compare the results of a social self-concept pretest and posttest; 3) to compare the social self-concept pretest and follow-up; and 4) to study the satisfaction level with the activities. The subjects consisted of 19 pre-service teachers studying in the Thai major in the second semester of academic year 2015. They were selected using simple random sampling. The approach consisted of 16 activities and which were operated for two days. The subjects were evaluated with the social self-concept of pre-service teacher inventory in three periods: the pretest, posttest and follow-up. The Wilcoxon Signed Rank Test was employed for quantitative data analysis. Moreover, content analysis was used for qualitative data from satisfaction survey (feeling and changes). The results were 1) the efficiency of activities based on contemplative approaches was 77.20/77.54 which was higher than the criterion. However, the effectiveness index (E.I.) was 0.46 which was less than the criterion. Moreover, the level of pre-service teachers’ satisfaction was 4.86 which was higher than the criterion, and 2) the social self-concept posttest was higher than the pretest at the .05 level of significance. Moreover, the social self-concept follow-up test was not different from the posttest at the .05 level of significance.